1996
DOI: 10.1161/01.atv.16.11.1347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fat Saturation on LDL Oxidation and Monocyte Adhesion to Human Endothelial Cells In Vitro

Abstract: Forty-two healthy men and women were subjected to four consecutive dietary periods differing in the fat content of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (n-6) [PUFA(n-6)] and (n-3) [PUFA(n-3)]. Plasma lipids, vitamin E, and in vitro LDL oxidation were examined during each period. Adhesion of human monocytes to cultured human endothelial cells was used as a functional test to identify differences in the biological properties of LDL from each dietary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
88
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 40 publications
6
88
0
5
Order By: Relevance
“…It was reported that LDL-induced monocyte adhesion to endothelial cells was lower during the MUFA period than each of the others and that resistance of LDL to oxidation was greatest during the MUFA period (31). The authors suggest that the modulation of LDL fatty acid composition was responsible for the differences in adhesion and showed a significant negative correlation between monocyte adhesion to endothelial cells and the oleic acid content of LDL (31). Expression of adhesion molecules by either cell type was not measured, but it is possible that this too may have played some role in the decreased adhesion during the MUFA period.…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 89%
See 1 more Smart Citation
“…It was reported that LDL-induced monocyte adhesion to endothelial cells was lower during the MUFA period than each of the others and that resistance of LDL to oxidation was greatest during the MUFA period (31). The authors suggest that the modulation of LDL fatty acid composition was responsible for the differences in adhesion and showed a significant negative correlation between monocyte adhesion to endothelial cells and the oleic acid content of LDL (31). Expression of adhesion molecules by either cell type was not measured, but it is possible that this too may have played some role in the decreased adhesion during the MUFA period.…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 89%
“…In an interesting study by Mata et al (31), healthy men and women living in a religious community were subjected to four consecutive dietary periods (isocaloric) differing in the fat content of SFA, MUFA and n-3 and n-6 PUFA. It was reported that LDL-induced monocyte adhesion to endothelial cells was lower during the MUFA period than each of the others and that resistance of LDL to oxidation was greatest during the MUFA period (31). The authors suggest that the modulation of LDL fatty acid composition was responsible for the differences in adhesion and showed a significant negative correlation between monocyte adhesion to endothelial cells and the oleic acid content of LDL (31).…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 95%
“…Other evidence in humans suggests that a MUFA-rich diet may indeed affect the process of cellular adhesion. In an interesting study by Mata et al (1996) healthy men and women living in a religious community were subjected to four consecutive dietary periods (isocaloric) differing in the fat content of SFA, MUFA and n-3 and n-6 PUFA. It was reported that monocyte adhesion to endothelial cells was lower during the MUFA period than each of the others and that resistance of low-density lipoprotein (LDL) to oxidation was greatest during the MUFA period (Mata et al, 1996).…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 99%
“…In an interesting study by Mata et al (1996) healthy men and women living in a religious community were subjected to four consecutive dietary periods (isocaloric) differing in the fat content of SFA, MUFA and n-3 and n-6 PUFA. It was reported that monocyte adhesion to endothelial cells was lower during the MUFA period than each of the others and that resistance of low-density lipoprotein (LDL) to oxidation was greatest during the MUFA period (Mata et al, 1996). The authors suggest that the modulation of LDL fatty acid composition was responsible for the differences in adhesion and showed a significant negative correlation between monocyte adhesion to endothelial cells and the oleic acid content of LDL (Mata et al, 1996).…”
Section: Effects Of Olive Oil On Expression Of Adhesion Moleculesmentioning
confidence: 99%
See 1 more Smart Citation